KEBUTUHAN MENCARI VARIASI MEMODERASI PENGARUH KEPUASAN PELANGGAN SMARTPHONE SAMSUNG TERHADAP NIAT BERPINDAH MEREK DI DENPASAR - Dwinanto, Rizki Rachmad; Suasana, I Gst. A. Kt. Gd. (E-Jurnal Manajemen; Vol 7 No 11 (2018)DO - 10.24843/EJMUNUD.2018.v07.i11.p12, 2018)
Smartphone users are now growing rapidly. Smartphone users in Indonesia are very diverse, start from children, teenagers to adults, and there are no gender and work limits. In Indonesia Samsung brand smartphones are not foreign to the public, Samsung still cement its position in the first rank of smartphone market share in Indonesia. This study aims to explain the effect of customer satisfaction on brand shifting intentions, as well as the role of the need to find variations to moderate the effect of customer satisfaction on the intention of switching brands on users of Samsung brand smartphone products in Denpasar City. This study uses non-probability sampling sampling technique with purposive sampling method, using 140 respondents who are users of Samsung brand smartphone products, and conducted in Denpasar City. This study uses data analysis techniques in the form of Moderated Regression Analysis. Based on the analysis, customer satisfaction has significant negative effect on brand switching intention. The results of this study also found that the need for variation can weaken the effect of customer satisfaction on brand switching intentions. The implications of this study are as an additional reference to further research relating to brand switching intent. On the other hand practical implications of this research is as an additional information for Samsung company to always innovate in accordance with the needs of variations from consumers.  Keyword: Customer Satisfaction, Variety Seeking, Brand Switching Intention.